2017
DOI: 10.1080/02640414.2017.1409855
|View full text |Cite
|
Sign up to set email alerts
|

Walk this way: validity evidence of iphone health application step count in laboratory and free-living conditions

Abstract: Several attempts have been made to demonstrate the accuracy of the iPhone pedometer function in laboratory test conditions. However, no studies have attempted to evaluate evidence of convergent validity of the iPhone step counts as a surveillance tool in the field. This study takes a pragmatic approach to evaluating Health application derived iPhone step counts by measuring accuracy of a standardized criterion iPhone SE and a heterogeneous sample of participant owned iPhones (6 or newer) in a laboratory condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 20 publications
3
68
0
1
Order By: Relevance
“…The observed compliance rate of >80% and mean wear time of 12.71 ± 1.13 h account for the validity of the measured step count. 22,23 Apart from activity monitoring, wrist-worn smart devices like the Apple Watch measure its wearer's heart rate via photoplethysmography. The observed underestimation and overestimation of high and low distances may at least in part be explained by the fact that the used iOS/watchOS devices have the highest accuracy at a pace of 5 km/h walking speed that is less good with slower walking pace.…”
Section: Validity Of Smart Device-based Measurement Of Health Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The observed compliance rate of >80% and mean wear time of 12.71 ± 1.13 h account for the validity of the measured step count. 22,23 Apart from activity monitoring, wrist-worn smart devices like the Apple Watch measure its wearer's heart rate via photoplethysmography. The observed underestimation and overestimation of high and low distances may at least in part be explained by the fact that the used iOS/watchOS devices have the highest accuracy at a pace of 5 km/h walking speed that is less good with slower walking pace.…”
Section: Validity Of Smart Device-based Measurement Of Health Datamentioning
confidence: 99%
“…The observed underestimation and overestimation of high and low distances may at least in part be explained by the fact that the used iOS/watchOS devices have the highest accuracy at a pace of 5 km/h walking speed that is less good with slower walking pace. 22,23 Apart from activity monitoring, wrist-worn smart devices like the Apple Watch measure its wearer's heart rate via photoplethysmography. For the Apple Watch 1, several trials give evidence of its good or very good accuracy in measuring heart rate under laboratory conditions.…”
Section: Validity Of Smart Device-based Measurement Of Health Datamentioning
confidence: 99%
“…In a free-living condition, steps were under-estimated by approximately 1,340 steps/day when averaged across observation days. [39] According to the study authors this likely reflects not carrying the iPhone continually throughout the day rather than inaccuracy in the step counting feature.…”
Section: Outcome Measuresmentioning
confidence: 94%
“…In a recent validation study of the iPhone step counting feature (version 6 or newer), it was found to be accurate in laboratory conditions [39]. In a free-living condition, steps were under-estimated by approximately 1,340 steps/day when averaged across observation days.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Inclusive, um estilo de vida menos ativo remete em problemas de saúde e está, certamente, relacionado com a diminuição dos passos diários de um indivíduo 4 , uma vez que, maior volume de passos diários é inversamente proporcional a obesidade em nível populacional 5 . Para avaliação dos passos diários, geralmente utiliza-se acelerômetros e pedômetros 6 , porém, o pedômetro tem sido usado com maior frequência por ter custo baixo e fácil aplicabilidade 7 . Assim, os passos diários monitorados por pedômetro demonstra-se como uma boa alternativa para controlar e avaliar de forma objetiva o NAFH 8 .…”
Section: Introductionunclassified